redesigning acoustic space at the Balikpapan Art building, East Kalimantan - ribka fransiska wewra; Jusuf Thojib (Jurnal Mahasiswa Jurusan Arsitektur, 2019)
A showcase can be enjoyed comfortably depending on the quality of the acoustic space.According to Suptandar (2004), it was said that the acoustic arrangement had a role and had a great influence on a show.One of the show space is the Balikpapan Art building, East Kalimantan which needs evaluation because the show room is a building that has the function of the first show in the region of Balikpapan, many art activities Held in the space.The research method employed is to use a quantitative approach of evaluative and the experimental quasi method to produce a redesign that can improve the quality of the acoustic chamber.Using the time calculation of the reverberation time and the level of sound pressure in the space, the calculated result stated at 500hz and 1000 Hz reverberation time 2.3 seconds and 2.1 seconds and the level The sound pressure is 53.7 Db.The redesign result of a buzzing time at 500 Hz is 1.45 seconds and at 1000 Hz is 1.71 seconds which is still in a count as per the standard drone time, for the sound pressure level of the redesign 33.83 Db and is already entered in the calculation of the existing standard for Create a good acoustic quality in the show room.